WIDYA MWAT YASA SEBAGAI IMPLEMENTASI BELA NEGARA DALAM MEMBENTUK JATI DIRI UPN “VETERAN” - Fajar Indra Nur Alam; Dody Pintarko; Taufikurrahman (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
University of Pembangunan Nasional (UPN) "Veteran" Indonesia has a philosophy reflected in its motto "Widya Mwat Yasa," which comes from Sanskrit and means "Knowledge to be dedicated to society." This philosophy emphasizes the importance of knowledge not solely for individual interests, but also for the welfare of society, the nation, and the state. UPN "Veteran" also has a strong identity as a "campus of national defense," inheriting the spirit of patriotism and devotion from the independence fighters. UPN "Veteran" students are educated to develop their academic potential while internalizing national defense values such as nationalism, discipline, and social responsibility. The philosophy of "Widya Mwat Yasa" serves as the foundation for implementing the three pillars of higher education: research, education, and community service, with the main goal of producing graduates and alumni who are not only academically excellent but also contribute to solving social problems. Service to society is an important aspect of education at UPN "Veteran," as reflected in various programs such as the Community Service Program (KKN) and community empowerment and service activities. With this spirit, UPN "Veteran" remains committed to producing competent future generations who are ready to contribute to the progress of Indonesia.